(Mis)trusted Contact: Resettlement Knowledge Assets and the Third Space of Refugee Reception - Kyriakides, Christopher; McLuhan, Arthur; Anderson, Karen; Bajjali, Lubna; Elgendy, Noheir (Refuge, 2019)
Drawing on interviews with 204 participants in two studies of privately sponsored refugee resettlement in Ontario, Canada, we explore the resettlement effects of pre-arrival contact on the interactional dynamics between private sponsors and privately sponsored Syrian refugees. Those who had regular pre-arrival contact via digital applications such as Facebook, Skype, and Whatsapp reported more positive, “successful” resettlement experiences than those who had not. This pre-arrival interactive dynamic has theoretical/conceptual implications beyond an understanding of the benefits of “information exchange.” Pre-arrival sponsor-sponsored interaction is not bound by the contexts of displacement or resettlement, but constitutes a “third space” of reception, co-created through trusted contact. We develop the concept of “resettlement knowledge assets” and report on how these assets emerge through pre-arrival trust building, modify the resettlement expectations of both sponsors and sponsored, and reduce resettlement uncertainty.